Identification of factors influencing patient satisfaction with orthopaedic outpatient clinic consultation: A qualitative study - Waters, S.; Edmondston, S.; Yates, P.; Gucciardi, Daniel (Churchill Livingstone, 2016)
Background: In recent years, new models of health service delivery in orthopaedic outpatient clinics, including physiotherapists working in orthopaedic triage roles, have become increasingly common. Evaluation of patient satisfaction with orthopaedic clinic services is dependent on an understanding of factors influencing patient satisfaction in this clinical context. Objectives: The objective of this study was to identify the factors influencing patient satisfaction with orthopaedic outpatient clinic services. Study Design: A cross-sectional, qualitative design including focus groups and interviews. Methods: Interviews and focus group sessions were undertaken with 36 participants representing patients, health professionals and clinical support staff in an orthopaedic outpatient clinic. Interviews and focus groups provided a rich narrative which was subjected to a process of thematic analysis. Results: The analysis identified seven themes influencing patient satisfaction with orthopaedic clinic assessment. These themes were clinic waiting time, clinical contact time, trust, empathy, communication, expectation and relatedness. Conclusions: Understanding factors influencing patient satisfaction is important to inform organisational and clinical processes that aim to foster high levels of patient satisfaction. Clinician awareness of the interpersonal issues which dominate stakeholders' perspectives of patient satisfaction may improve the patient experience and potentially foster patient behaviours toward a therapeutic advantage. An understanding of these factors in the context of orthopaedic clinics is also important in the development of questionnaires designed to evaluate patient satisfaction with health service delivery.